A review on zeolite catalyst for deNOx performance in ammonia–selective catalytic reduction. (15th February 2023) - Sunil Kumar, M.; Alphin, M.S.; Senthil Kumar, P.; Raja, S.
Highlights: NOx conversion efficiency was influenced by metal substituted zeolite. In the low temperature window, Cu-Z has a greater tendency than Fe-Z to recover active sites. SAR value of zeolite will determine the efficiency of selective catalytic reduction. Abstract: Internal combustion (IC) engines rely heavily on NOx emissions. Various studies are being conducted to lower NOx emission in order to achieve the BS-VI norms. This review examines a zeolite catalyst using metal substitutes, primarily copper Cu, and iron Fe, and compares it to a commercial vanadium catalyst in terms of deNOx efficiency and deactivation process. Based on the size of pores of zeolite, it has been classified into large size, medium size and small size zeolites. At low temperature, small pore zeolite with Cu substituted has better deNOx efficiency with higher thermal stability with high-temperature reaction conditions. Whereas, Cu-SSZ-13 & Cu-SAPO-34 exhibits wider temperature window and also exhibits good thermal stability even below 350 °C. Si/Al ratio (SAR) plays a vital role in deNOx efficiency.